Mit KI (Elicit) den Forschungsstand beschreiben – ein kritischer Erfahrungsbericht - Schmidt, Rebecca (Sozialwissenschaftliche Methodenberatung)

Participatory Research with Teachers - A Critical Analysis of Power Dynamics - Schmidt, Rebecca (Transdisziplinäre Räume in den Kulturwissenschaften)

Critical Edtech Studies. Defining the field; envisioning the future. 2025 Position statement after the inaugural edition of the European Conference on Critical Edtech Studies (ECCES). - Decuypere, Mathias; Hartong, Sigrid; Joecks, Lucas; Knox, Jeremy; Ortegón, Carlos; Schmidt, Rebecca; Williamson, Ben
kein Abstract vorhanden

KI als Herausforderungen für die qualitative Methodenlehre – ein Diskussionsaufruf! - Schmidt, Rebecca (Sozialwissenschaftliche Methodenberatung)

Forschendes Lehren und Lernen unter der Bedingung von Digitalität – Vorstellung zweier Seminarkonzeptionen - Schmidt, Rebecca; Peters, Laura N. (Digitale Prüfungsszenarien in der Hochschule)
Dieser Beitrag stellt zwei Seminarkonzeptionen vor, in welchen technisch-didaktische Vorüberlegungen, Lehr-/Lernaktivitäten und Prüfmodalitäten unter der Bedingung von Digitalität skizziert werden. Es wird das digitale wissenschaftliche Lesen und Schreiben ins Zentrum der Interaktion mit digitalen Technologien gestellt. In den Se minaren wurden von Studierenden selbstständig Daten (Text) gesammelt, ausgewertet und geclustert. Die kollaborative cloudbasierte Speicherung der Seminardaten, der Einbezug einer geteilten Literaturdatenbank sowie der Einsatz der Notizsoftware Obsi dian.md beim gemeinschaftlichen wissenschaftlichen Lesen und Schreiben wurden er probt. Zentrale Herausforderung war die Doppelrolle der Dozierenden (Verantwor tung für Lehr-/Lernsetting vs. Techniksupport). Herausragend war die Partizipation und Verantwortungsübernahme der Studierenden in den Seminarsitzungen und beim Peersupport.
Keywords: Digitales wissenschaftliches Schreiben; Forschendes Lernen; Digitalität; Digitales Konzeptverstehen; Lehrer:innenbildung; Digital Literacy

The Bot Delusion. Large language models and anticipated consequences for academics’ publication and citation behavior - Wieczorek, Oliver; Steinhardt, Isabel; Schmidt, Rebecca; Mauermeister, Sylvi; Schneijderberg, Christian (Futures)
The present paper discusses the extent to which Large Language Models (LLMs) may affect the scientific enterprise, reinforcing or mitigating existing structural inequalities expressed by the Matthew Effect and introducing a “bot delusion” in academia. In a theory-led thought experiment, we first focus on the academic publication and citation system and develop three scenarios of the anticipated consequences of using LLMs: reproducing content and status quo (Scenario 1), enabling content coherence evaluation (Scenario 2) and content evaluation (Scenario 3). Second, we discuss the interaction between the use of LLMs and academic (counter)norms for citation selection and their impact on the publication and citation system. Finally, we introduce communal counter-norms to capture academics’ loyal citation behavior and develop three future scenarios that academia may face when LLMs are widely used in the research process, namely status quo future of science, mixed-access future, and open science future.
Keywords: Large Language Models; Matthew Effect; Academic Publishing and Citation Systems; Scientific Norms; Thought Experiment

Automatische Transkriptionssoftware - ein Erfahrungsbericht - Schmidt, Rebecca (Sozialwissenschaftliche Methodenberatung)

Open Research Practices and Cultural Change: A Commentary on “(Why) Are Open Research Practices the Future for the Study of Language Learning?” - Steinhardt, Isabel; Mauermeister, Sylvi; Schmidt, Rebecca (Language Learning)
Keywords: Open Science; Open Science Practices; Cultural Change

The Bot Delusion. ChatGPT and anticipated consequences for research communication - Wieczorek, Oliver; Steinhardt, Isabel; Schneijderberg, Christian; Schmidt, Rebecca; Mauermeister, Sylvi
The reproduction of social inequalities through artificial intelligence (AI) and machine learning via artificial neural networks (ANN) has been demonstrated empirically in various areas of society, for instance in policing and personnel hiring decisions. Yet, a broader discussion is missing to what extent ANN technological developments may affect the scientific enterprise and reinforce or mitigate existing structural inequalities in academia. Focusing on publications and citations as main currencies in science, the anticipated consequences of ChatGPT on the research communication of existing and new knowledges are discussed in three scenarios, which echo the social structures in academia.

Grenzüberschreitung und Distanzierung – Geschlechterforschung in universitären Toiletten - Krollmann, Rabea; Schmidt, Rebecca; Spill, Annika (blog interdisziplinäre geschlechterforschung)